THEORETICAL FOUNDATIONS AND MODERN TRENDS OF INCLUSIVE EDUCATION (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the theoretical foundations of inclusive education, its essence and modern development trends. The main goal of inclusive education is to ensure the right of all children, including those with disabilities or special needs, to receive education on equal terms. The study highlights the principles of humanity, equality, tolerance and cooperation as important factors in the development of inclusive education. It also analyzes reforms in the implementation of an inclusive approach in the education system of Uzbekistan, international experiences and the processes of introducing new pedagogical technologies. At the end of the article, promising directions for improving inclusive education are identified.